Utilization and Contribution of Non-Timber Forest Products to the Community Economy in Sentajo Protected Forest - Suhada, Nur; Somadona, Sonia; Dilas, Akbar Alldhu (Jurnal Natur Indonesia, 2025)
The potential of Non-Timber Forest Products (NTFPs), in general has not been optimally utilized. The processing of NTFPs for the people of Koto Sentajo Village is still not the primary source of income for the community but is part of fulfilling daily living needs. This study aims to determine the types of NTFP utilization and their contribution to the economy of the community in Koto Sentajo Village. This study uses a qualitative descriptive approach, and primary data were collected through observation and in-depth interviews using purposive sampling techniques. Data were analyzed quantitatively. The results of this study found that the types of NTFPs utilized by the people of Koto Sentajo Village are fruits and medicinal plants; the types of fruits are keranji (Dialium indum), tampui (Baccaurea macrocarpa), geruntang (Phoebe grandis), cempedak (Artocarpus fretessii), forest durian (Durio zibethinus), kulim (Scrodocarpus borneensis), petai (Parkia speciosa), and barangan (Castanopsis argentea). In contrast, the types of medicinal plants most widely utilized are sepico (Eurycoma longifolia Jack) and rosam (Dicranopteris linearis). The contribution of NTFPs to the people's economy in Koto Sentajo Village is 5.6% of the total income of the community, or around IDR 1,519,851/person/year, to the average total income of IDR 26,983,265/person/year